2010
DOI: 10.1007/s00198-009-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum osteopontin is a risk factor for osteoporosis in menopausal women

Abstract: Serum OPN levels could be used as a biomarker for the early diagnosis of osteoporosis in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 41 publications
8
66
3
1
Order By: Relevance
“…Our previous study indicated that plasma OPN levels could be used as a biomarker for the early diagnosis of osteoporosis in postmenopausal women [34]. In this study, we demonstrated that there is a sequential decrease in the plasma OPN level with the improvement in concomitant bone mineral density after intermittent PTH treatment in women with postmenopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our previous study indicated that plasma OPN levels could be used as a biomarker for the early diagnosis of osteoporosis in postmenopausal women [34]. In this study, we demonstrated that there is a sequential decrease in the plasma OPN level with the improvement in concomitant bone mineral density after intermittent PTH treatment in women with postmenopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 52%
“…Our previous study indicated that plasma OPN levels could be used as a biomarker for the early diagnosis of osteoporosis in postmenopausal women [34].…”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin is a protein that preferentially accumulates at mineralised tissue interfaces [41] and plays an important role in regulating osteoclastogenesis and is thereby often used as an indicator of bone turnover [42]. One recent study has suggested that over-expression of osteopontin is a risk factor for osteoporosis [43] and bone loss is suppressed in OPN-deficient mice following ovariectomy, despite an increase in osteoclastogenesis [44]. In the current study, we show for the first time that estrogen deficiency induced an increase in osteopontin expression which remained elevated over time and that these changes occurred prior to significant changes in bone microarchitecture.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that OPN may facilitate the adhesion (or detachment) of the osteoclast to the bone surface and act as a signaling molecule or a scaffold in normal bone metabolism and turnover [22,25,26]. In human, high OPN levels have been indicated as a risk factor for low bone mineral density in postmenopausal women and used as a biomarker for early osteoporosis diagnosis [27]. Studies have shown that a high level of osteopontin mRNA and protein expression occurs in both intramembranous and endochondral ossification, as well as remodeling bone, including the human osteophyte [28].…”
Section: Discussionmentioning
confidence: 99%